182. Successes of a System-directed and Multi-faceted Inpatient Antimicrobial Stewardship Program in a Large, Integrated Delivery Organization. (26th November 2018) - Colley, Peter; Thyagarajan, Rema; Nguyen, Hoa; Masica, Andrew; Storey, Donald
Abstract: Background: In 2015, Baylor Scott and White Health (BSWH) implemented a system-wide antimicrobial stewardship program (ASP) across 22 acute care facilities. The ASP committee, led by an Infectious Diseases (ID) Physician and ID Pharmacist, includes membership of health system leadership, facility-specific ID physician and clinical pharmacy leaders, informatics, infection control, and microbiology. The committee's purpose was to facilitate local implementation of antimicrobial stewardship interventions recommended by the Centers for Disease Control and Prevention and to improve antimicrobial use at BSWH. Methods: The ASP created and approved antibiotic use guidelines (carbapenems, vancomycin, daptomycin, fluoroquinolones), policies, and set performance goals related to antibiotic use, which were then implemented locally at each facility. Beginning July 2016, all 22 acute care facilities went live with a clinical decision support (CDS) tool, a mobile device platform for physician access to ASP guidelines, and a requirement for antibiotic review at 48–72 hours. The CDS software also provided tracking of utilization data as days of therapy (DOT) standardized to 1, 000 patient-days at risk (DAR) at the local facility and health system levels. The ASP committee tracked and reported metrics on the usage of total and targeted antibacterials, with comparisons in usage made between fiscal years (FY) 2017 and 2018. Means of total antibacterial usage and targeted antibiotics were compared between July to March of each FY using t -tests. Results: Mean total antibacterial usage for the BSWH system was 649.6 vs. 622.6 DOT/1, 000 DAR for FY17 and FY18, respectively (difference-Δ: 27.0; CI 95%: 7.9–46.1; P = 0.008). Mean targeted antibacterial usage (in DOT/1, 000 DAR, FY17 vs. FY18) was 100.2 vs. 92.8 for vancomycin (Δ: 7.4; CI 95%: 5.0–9.9; P < 0.001), 30.4 vs. 20.7 for carbapenems (Δ: 9.7; CI 95%: 7.2–12.3; P < 0.001), 80.1 vs. 60.1 for fluoroquinolones (Δ: 20.0; CI 95%: 17.1–22.9; P < 0.001), and 4.6 vs. 4.4 for daptomycin (Δ: 0.2; CI 95%: -0.5–1.0; P = 0.454). Conclusion: BSWH has made significant progress in reducing targeted and overall total antibacterial usage through the implementation of an enterprise-level antimicrobial stewardship program using a multifaceted approach. Disclosures: All authors: No reported disclosures.